Analysis of clinical and molecular genetic characteristics of Wiskott-Aldrich syndrome and X-linked thrombocytopenia - TURCAN, Doina; ANDRIES, Lucia; DORIF, Alexandr; SACARA, Victoria (One Health & Risk Management, 2021)
Introduction. Wiskott-Aldrich syndrome is a rare X-linked disorder characterized by microthrombocytopenia, eczema, and recurrent infections. It is caused by mutations of the WAS gene which encodes the WAS protein (WASp) – a key regulator of actin polymerization in hematopoietic cells. Mutations within the WASp gene result in a wide heterogeneity of clinical disease, ranging from ‘classical WAS’ to mild asymptomatic thrombocytopenia (X-linked thrombocytopenia [XLT]), or congenital neutropenia (X-lined neutropenia [XLN]). Case presentation. This present paper reports a phenotypical and laboratory description of two children diagnosed with WAS and one child diagnosed with XLT. The first case was a six months old male with septicemia, thrombocytopenia, eczema and petechial rash. The second case was a 2 years old boy presenting with complaints of recurrent infections, eczema and thrombocytopenia with small platelet size. The third case was a 16 years old boy who presented with thrombocytopenia and recurrent sinopulmonary infections. Conclusions. Due to a wide spectrum of clinical ﬁndings, the diagnosis of WAS/XLT should be considered in any male patient presenting with petechiae, bruises, and congenital or early-onset thrombocytopenia associated with small platelet size.